Dari Gurun Menuju Sungai: Kohesi Sosial di Kampung Arab Kota Banjarmasin - Noprianu, Hawi; Budhi, Setia (Prodi Sosiologi FISIP ULM, 2024)
Hadhrami Arabs in Banjarmasin City live with a blend of Arab and Banjar cultures as a symbol of unity in community life that permeates social, religious, cultural and business life elements. This study aims to describe the lives of ethnic Arabs who inhabit the West Antasan Kecil Street area, Banjarmasin City, in terms of religion, socio-culture, and economic development. The method used is qualitative, with data collection techniques namely observation, interviews, and documentation. Data analysis techniques used data reduction, data presentation and conclusions. This research shows that the socio-cultural community of Kampung Arab is classified as a multicultural society. Arabic and local cultures combine in elements of daily life, such as language, architecture, food and art also acculturate to form a new culture. In the field of architecture, the exterior uses Banjar architecture, while the interior uses Arabic architecture. As for the mosque, it fully uses Arabic architecture. In terms of business, Arabs and non-Arabs (Banjar and local migrants) work together to develop the tourism, culinary and livestock sectors. Individuals within a community group are bound by a goal, namely financial gain and brotherhood as a community. Whether in the religious, cultural or commercial/business spheres, the involvement of ethnic Arabs and local ethnicities has always occurred, from the past to the present. Social cohesion and solidarity are maintained so as to produce a potential and uniqueness of its own, and all starts from the intention or goal for the good in the future.